GE3D: A Virtual Campus for Technology-Enhanced Distance Learning - Grieu, Jean; Lecroq, Florence; Person, Patrick; Galinho, Thierry; Boukachour, Hadhoum (International Journal of Emerging Technologies in Learning (iJET), 2010)
A lot of learning systems platforms are used all over the world. But these conventional E-learning platforms aim at students who are used to work on their own. Our students are young (19 years old â?? 22 years old), and in their first year at the university. Following extensive interviews with our students, we have designed GE3D, an E-learning platform, according to their expectations and our criteria. In this paper, we describe the studentsâ?? demands, resulting from the interviews. Then, we describe our virtual campus. Even if our platform uses some elements coming from the 3D games world, it is always a pedagogical tool. Using this technology, we developed a 3D representation of the real world. GE3D is a multi-users tool, with a synchronous technology, an intuitive interface for end-users and an embedded Intelligent Tutoring System to support learners. We also describe the process of a lecture on the Programmable Logic Controllers (PLCâ??s) in this new universe.